L’accommodation dans le débat politique britannique Question Time. Quelle modélisation pour quelles stratégies ? - Laurent Rouveyrol (Anglophonia)
This article explores the notion of accommodation in a corpus composed of transcripts of the panel debate Question Time. Accommodation is generally considered as a multi-faceted notion, originating from sociolinguistics and psychology. The aim of the present study is twofold: first we would like to propose a conceptual framework based on Vion’s research on interaction processes (1992, 1995, 1998). Dwelling on the concept of “positioning processes” (rapports de places) this framework enables us to encompass a wide range of discursive and linguistic phenomena observable in mediatized interaction, ranging from macro to micro orders, such as the “enunciative staging processes”, by which speakers achieve different degrees of involvement in their speech. Second, we intend to explore the notion of accommodation arguing that it is intrinsically genre sensitive. A televised debate such as Question Time is by nature a complex type of interaction formed of two components: an internal level (the interaction in the studio), and an external one destined to viewers behind their television sets. Several examples of accommodating strategies will be analysed, notably in relation to opposition and planning strategies. A debate is also a contradictory genre in the way that a certain degree of opposition is to be expected, which turns divergent accommodation into a convergent strategy. It will be argued that the mode of opposition is gradual and corresponds to a continuum. Planning strategies will also be explored and we will consider that the “ double inverted pyramid structure” is a case of convergent accommodation induced by the debate genre.